Reconnecting divided urban spaces through cross-border cooperation in the Bulgarian-Greek borderland - Korkmaz, Nuri (Routledge Journals, Taylor & Francis Ltd, 2025)
Europeanization and its impact on Southeast Europe remain subjects of ongoing debate. Each round of European Union enlargement has introduced new challenges, as macro-political agendas often failed to address localized, micro-level issues. The Bulgarian-Greek border region serves as a compelling case for examining both the potential and the limitations of the EU's transformative power. The cities of Kardzhali (Bulgaria) and Komotini (Greece) offer valuable empirical insights into the dynamics of cross-border cooperation. Decades of Cold War division entrenched the perception of a hard border in the region - an obstacle that persisted even after Bulgaria acceded to the EU and continues to shape the Europeanization process. Although much remains to be done, significant progress is evident in the everyday interactions within the urban spaces of Kardzhali and Komotini.
Keywords: Bulgarian-Greek borderland; Europeanization; cross-border cooperation; Balkans; southeast Europe